Operating Thermal Power Plants Efficiency Improvement under Current Conditions - V. V. Yanchuk; V. N. Romaniuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In the present-day conditions, the issue of energy saving is becoming increasingly acute and permanently relevant. This situation is caused by rapid growth in prices for primary energy resources and by the need to reduce the share of natural gas in the incoming part of the energy balance of Belarus. According to available statistics, with the commissioning of the Belarusian NPP, the share of natural gas in the incoming part of the energy balance decreases from 97 to 59 %. In the economic complex, the share of this primary energy resource is projected at 70 %. The problem of energy saving is solved most rationally and with the least investment only by increasing the efficiency of natural gas use, especially due to the commissioning of the Belarusian NPP, the issue of preserving the possibility of using centralized heating facilities is acute. It is necessary to increase the thermodynamic efficiency of the cycles of steam turbine plants, both heating and condensing, which form the basis of the generation of the Belarusian power system, in order to restore the energy characteristics of the power system, which have somewhat decreased with the commissioning of the NPP. In the limit, the share of natural gas in the incoming part of the energy balance should be reduced to values not exceeding 50 %, in accordance with the requirements of energy security. The article considers examples of utilization of low-temperature secondary energy flows occurring at thermal power plants: the heat of the cooling processes of the generator, lubrication systems, as well as the heat of condensation of turbine exhaust steam and deeper cooling of flue gases. On the basis of this review, it is expected to identify promising areas of relevant research in relation to the energy system of Belarus.